Pengaruh Model Pembelajaran Make A Match Berbasis Penilaian Portofolio Terhadap Hasil Belajar IPA - Evita Wulandari, Komang; Suarni, Ketut; Tanggu Renda, Ndara (Universitas Pendidikan Ganesha, 2018)
This research is based on the problem about low learning result in science subject and the lack utilization of innovative learning model. The purpose of this research is to know the difference of science learning result between the students who learned with Make a match model based on portfolio assessment and conventional model. The type of this study was quasi experimental research with non-equivalent design post-test only control group design. Populations of the study are 120 5th grade students in SD Gugus VIII, Kecamatan Sawan, Kabupaten Buleleng in the School Year of 2017/2018. The samples of the study are the 5th grade students of SD Negeri 1 Sudaji and the 5th grade students of SD Negeri 2 Sudaji. The data were collected by using a multiple choice instrument and analyzed using descriptive statistical analysis and t-test inferential statistic. The result showed that t count = 4,349 and t table (at 5% significant level) = 2,011. It means that the Make a Match learning model based on portfolio assessment affects learning result of science subject of 5th grade students in SD Gugus VIII, Kecamatan Sawan, Kabupaten Buleleng, School Year of 2017/2018.